Transvaginal ovarian drilling followed by controlled ovarian stimulation from the next day improves ovarian response for the poor responders with polycystic ovary syndrome during IVF treatment: a pilot study - Bufang Xu; Mingjuan Zhou; Meiyu Cheng; Dan Zhang; Xian Wu; Chenchen Si; Lan Xia; Huihui Xu; Jian Li; Hsun-Ming Chang; Peter C. K. Leung; Aijun Zhang (BMC, 2020)
Abstract Background Poor response patients with PCOS who are not susceptible to gonadotropin stimulation are more likely to have canceled cycles or poor clinical outcomes during IVF treatment. However, some limitations exist in the present therapies. In this study, we evaluated the effects of using the transvaginal ovarian drilling (TVOD) followed by controlled ovarian stimulation (COS) from the second day of these poor responders. Methods During IVF, 7 poor responders with PCOS and 28 PCOS patients (14 normal and 14 high responders) were recruited. All patients received COS with the gonadotropin-releasing hormone antagonist protocol. For the poor responders, after undergoing 10 to 14 days of ovulation induction with no response, the TVOD was applied and then ovarian stimulation was performed from the next day at the same gonadotropin dose. Serum samples during COS and follicular fluid samples from the dominant follicles on the oocyte pick-up (OPU) day in all three groups were collected. Besides, follicular fluid from small follicles (diameter < 1 cm) in the normal and high responders on the OPU day and those in the poor responders on the TVOD day were gathered. Hormonal levels were examined in all samples using immunometric assays. Results All the poor responders restored ovary response after receiving TVOD. There was no significant difference in the stimulation duration, total gonadotrophin dose used and the clinical outcomes among the three groups. The body mass index, serum and follicular levels of anti-Müllerian hormone (AMH) and testosterone in poor responders were higher than those in the other two groups, and the application of TVOD significantly decreased the levels of AMH and testosterone in both serum and follicular fluid. Conclusions TVOD followed by ovulation induction from the next day is effective and convenient for poor responders with PCOS. The decline of AMH and testosterone resulted from TVOD may be the main reason resulting in the recovery of ovary sensitivity to gonadotropins. The small sample size is the primary limitation of this study, future studies using a large population cohort and monitoring the long-term outcomes of this strategy will be required. Trial registration ChiCTR1900023612. Registered 04 June 2019-Retrospectively registered.